P1149PERITONEAL MEMBRANE CHARACTERISTICS OVER TIME: A LONGITUDINAL STUDY. (6th June 2020) - Balafa, Olga; DUNI, ANILA; Tseke, Paraskevi; Rapsomanikis, Karolos Pavlos; Oikonomou, Margarita; Pappas, Haralambos; Theodorou, Ioanna; Ntounousi, Evangelia
Abstract: Background and Aims: Modified PET (use of 3.86% glucose dialysate instead of 2.27%) and temporal drainage at one hour allows a more complete study of peritoneal membrane transport, as it provides information about sodium sieving, free water transport (FWT) and ultrafiltration failure (UFF). Longitudinal data using this PET are sporadic. Aims of our study were a) longitudinal follow-up of the membrane function using modified PET b) evaluation of UFF and association with clinical and membrane characteristics. Method: We analyzed all modified PET tests performed in our unit during the last 9 years. Patients who underwent the first test during the first year of treatment and then once a year were included. We estimated classic peritoneal transport parameters like D/P creatinine, D/D0 glucose and ultrafiltration (UF) at 4 hours. Moreover we calculated sodium seiving expressed as Dip/DPNa= (Dialysate sodium time 0/plasma sodium)-(Dialysate sodium time 1 hour/plasma sodium)], sodium removal (in one hour) and FWT. We collected clinical and lab data of the patients too. Results: A total of 219 PETs were performed in 85 PD patients, (median age 64 years (range 18-45). The baseline membrane characteristics of the patients were: DP creatinine=0.74±0.11, D/D0glucose=0.28±0.08, DipDPNa=0.05±0.04, sodium removal=29, 804 ±26, 894 (mmol/L), FWT=214.9±194.7 ml and UF =655.1±265.5 ml. On multivariate regression analysis D/P creatinine, FWT and sodium removal were significant independent covariates accounting for 50% of the variability of ultrafiltration . The patients were followed-up for a median of 36 months (range 2.4-143).For the repeated measurements, the analysis showed that the observed values of D/Pcre, D/D0, Dip/DPNa, FWT and UF remained rather stable across the different time measurements. During the study, 23 out of 85 pts developed peritoneal UF failure (UFF). Analysis was performed using univariate random effects logistic time-series models and only D/D0 (OR=0.84, P=0.001), D/P Cre (OR=1.15, p<0.001), urine volume (OR=1.26, p=0.027) and sodium removal (OR=0.99, p=0.003) were significantly associated with relative risk of UFF development. Conclusion: Surprisingly, our patients present a stable membrane function over time. Possible explanations could be the low peritonitis rate and strict use of hypertonic glucose dialysates. Ultrafiltration failure was correlated with higher D/P creatinine and lower D/D0 glucose values, higher baseline urine volume and lower sodium sieving.